PENGEMBANGAN MEDIA RODA PUTAR UNTUK MENINGKATKAN KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK USIA DINI - Lailatul Zurlita; Yuhasriati .; Siti Naila Fauzia; Israwati .; Sitti Muliya Rizka; Suhartati .; Rahmatun Nessa (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2022)
Keywords: Media, Spinning Wheel, Geometric Shapes, Early ChildhoodThe use of media is very important in increasing the ability to recognize geometric shapes in early childhood. Improving the ability to recognize geometric shapes is one level of achievement of children's development in the scope of cognitive aspects. The rotary wheel can be used as a medium to help improve the ability to recognize geometric shapes in early childhood. The rotating wheel media is a media specially designed to improve the ability to recognize geometric shapes in early childhood, which is circular in shape, has a pole as a support, and has a circle width of 54 cm and a pole height of 67 cm, has 5 parts, where each part contains one geometric shape (circle, square, triangle, rectangle, and rhombus). This research is a type of research and development research and development (RD) that aims to produce a rotating wheel to improve the ability to recognize valid early childhood geometric shapes. The data collection in this study was carried out through a study of literature and a questionnaire sheet validation of learning media for media experts and material experts. The development of the initial concept in this study consisted of three stages, namely: the stage of defining, designing and developing. The results of the validation of the rotating wheel media by media experts get a final score of 98% with a very valid category. Meanwhile, the material expert obtained a final score of 100% with a very valid category. Based on the score of the validation results, it can be concluded that the rotating wheel media is very valid and can be used as a learning medium for early childhood to improve the ability to recognize geometric shapes. This research was only carried out until the media validation stage, for the product testing and distribution stage, further research will be carried out.Abstrak. Penggunaan media sangat penting dalam meningkatkan kemampuan mengenal bentuk geometri pada anak usia dini. Meningkatkan kemampuan mengenal bentuk geometri merupakan salah satu tingkat pencapaian perkembangan anak dalam lingkup aspek kognitif. Roda putar dapat digunakan sebagai media untuk membantu meningkatkan kemampuan mengenal bentuk geometri pada anak usia dini. Media roda putar adalah media yang dirangcang khusus untuk meningkatkan kemampuan mengenal bentuk geometri pada anak usia dini, yang berbentuk bundar, memiliki tiang sebagai penyangga, dan mempunyai lebar lingkarannya 54 cm dan tinggi tiangnya 67 cm, memiliki 5 bagian, dimana masing-masing bagian memuat satu bentuk bangun geometri (lingkaran, persegi, segitiga, persegi panjang, dan belah ketupat). Penelitian ini merupakan jenis penelitian pengembangan Research and Development (RD) yang bertujuan menghasilkan roda putar untuk meningkatkan kemampuan mengenal bentuk geometri anak usia dini yang valid. Pengumpulan data dalam penelitian ini dilakukan melalui studi literatur dan lembar angket validasi media pembelajaran untuk ahli media dan ahli materi. Pengembangan konsep awal pada penelitian ini terdiri dari tiga tahap yaitu: tahap pendefinisian, perancangan dan pengembangan. Hasil validasi media roda putar oleh ahli media mendapatkan skor akhir sebesar 98% dengan kategori sangat valid. Sedangkan oleh ahli materi memperoleh skor akhir sebesar 100% dengan kategori sangat valid. Berdasarkan skor hasil validasi tersebut dapat disimpulkan bahwa media roda putar sangat valid dan dapat digunakan sebagai media pembelajaran bagi anak usia dini untuk meningkatkan kemampuan mengenal bentuk geometri. Penelitian ini hanya dilakukan sampai tahap validasi media, untuk tahap uji coba produk dan penyebaran akan dilakukan pada penelitian lebih lanjut.Kata Kunci: Media, Roda Putar, Bentuk Geometri, Anak Usia Dini